2019
DOI: 10.2135/cropsci2018.03.0209
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Missing Values on Variance Component Estimates in Multienvironment Trials

Abstract: Multienvironment trials (METs) are conducted to evaluate cultivars across locations and years with often incomplete data structure due to annual cultivar replacements. The imbalance could cause biased variance component (VC) estimates depending on data dimension, proportion of missing values, and the cultivar dropout mechanism. The objective of this study was to quantify the bias of VC estimates obtained from imbalanced datasets. We performed simulations of METs with different data dimensions (number of cultiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(72 citation statements)
references
References 34 publications
7
62
1
2
Order By: Relevance
“…The current simulation as well as the simulation presented in Aguate et al (2019) variances for all random terms and the error. Note that the data were not re-analysed for the current study and therefore VCs were directly taken from Aguate et al (2019).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The current simulation as well as the simulation presented in Aguate et al (2019) variances for all random terms and the error. Note that the data were not re-analysed for the current study and therefore VCs were directly taken from Aguate et al (2019).…”
Section: Discussionmentioning
confidence: 99%
“…Note that the current simulation with BLUP-based selection matches Scenario 1 in Aguate et al (2019) as this scenario showed largest effects on relative bias and root mean square error (RMSE). The authors used four scenarios with the same type of imbalance but increased the size of the data by adding more genotypes and/or more locations compared to Scenario 1.…”
Section: Simulation Studymentioning
confidence: 93%
See 3 more Smart Citations